(untitled) (Ágora Journal, 2023)
The present study aims to observe some displacements that the Brazilian theatrical historiography about the nineteenth century experienced, through uses and articulations that made the dramaturgical element. If, in the nineteenth century, the presence of the director/director emerges as a possibility of untying between the scenic and the text, that is, text and spectacle are distinguished, which to some extent resulted in greater autonomy of the elements of the scene, how in the history of theater in Brazil we observe this cross between theater, dramaturgy and historiography? This article seeks to understand how some uses and articulations attributed to dramaturgy within the history of theater can indicate about continuities and ruptures of the field, as well as the overcoming of the text/scene dichotomy in the analysis of nineteenth-century theatrical manifestations.